Clozapine Use During Pregnancy and Lactation: A Case-Series Report - Imaz, M. Luisa; Oriolo, Giovanni; Torra, Mercè; Soy, Dolors; García-Esteve, Lluïsa; Martin-Santos, Rocio (Frontiers in Pharmacology, 2018)
The current prescription of clozapine in psychotic women of reproductive age makes it crucial to understand its pharmacokinetics during pregnancy and lactation as well as its risk profile for neonatal outcome. The aim of this case series was to provide new evidence on the pharmacokinetic features of clozapine that determine its passage through the placenta and amniotic fluid, as well as the neonatal clozapine elimination half-life (t1/2). This case series demonstrates for the first time that clozapine might show partial placental passage similar to other atypical antipsychotics. Clozapine levels decreased during the first few days in nursing infants. The half-life of clozapine in neonates was slightly higher than previously estimated. Clozapine use in pregnancy may be associated with diabetes mellitus, especially if there is a family history of this disease. Although no acute toxicological effects were observed in the intrauterine exposed newborn, close follow-up of pregnancy is recommended. However, these results must be taken with caution being a case series with small sample size.